Impact Evaluation of Child Labor on Health in Next 7 and 14 Years in Indonesia - Febri Hamdani; Eny Sulistyaningrum (Politeknik Statistika STIS, 2021)
This study aims to determine the impact of child labor on children's health both in next 7 and 14 years. Using two health indicators, growth in height and lung capacity. Child labor indicator is using child working hours. Three waves of longitudinal data from the Indonesian Family Life Survey (IFLS) are used, IFLS-3, IFLS-4, and IFLS-5. In addition to the child labor variable as the focus of this study, other variables are also used as control. The technique of analysis used is the Instrumental Variable where the head of the household’s education as the instrument variable. The robustness check is also performed to ensure the model. The analysis shows that in next 7 years, child labor has less effect on health. Child labor negatively affects height growth but does not affect lung capacity. However, in next 14 years child labor negatively affects health, for both height growth and lung capacity. This is confirmed by the result of the robustness check, where child labor is preponderant in next 14 years than 7 years.